PENGARUH LEARNING START WITH QUESTIONS TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA SD PADA MATERI CERMIN - Mariyana, Gina; Gusrayani, Diah; Panjaitan, Regina Lichteria (Jurnal Pena Ilmiah, 2017)
The reserach based on to know chritical thingking skill of high, middle, dan low group student through learning start with questions. The sample of this research is V class student of 95 students from Margamukti Elementary School, Mandalaherang Elementary Scholl I, adn Mandalaherang Elementary School II. The method used is pre-experimental and one-group-pretest-posttest design wth the same treatment from three schools. Instrumen used on the research is KAIPA test chritical thinking skills test, teacher performance observation, student activity observation, and questionnaire. Result of research using significance level Â showed that each group can improve chritical thingking skill with learning start with questions. The results showed that high group chritical thinking skill with is better than middle and low group, and middle group chritical thinking skills is better than low group